Secrets of the Titanic [videorecording] - Ballard, Robert D.; Huley, Graham; Kane, Dennis B.; Noxon, Nicolas (National Geographic Society special, 1986)
Highlights the century's underwater exploration, Dr. Robert Ballard of Woods Hole Oceanographic Institution and a learn of researchers located the S.S. Titanic since its sinking more than 70 years ago.